Projections of Global Delta Land Loss From Sea‐Level Rise in the 21st Century. Issue 14 (21st July 2021) - Nienhuis, Jaap H.; van de Wal, Roderik S. W.
Abstract: River deltas will likely experience significant land loss because of relative sea‐level rise (RSLR), but predictions have not been tested against observations. Here, we use global data of RSLR and river sediment supply to build a model of delta response to RSLR for 6, 402 deltas, representing 86% of global delta land. We validate this model against delta land area change observations from 1985–2015, and project future land area change for IPCC RSLR scenarios. For 2100, we find widely ranging delta scenarios, from +94 ± 125 (2 s.d.) km 2 yr −1 for representative concentration pathway (RCP) 2.6 to −1, 026 ± 281 km 2 yr −1 for RCP8.5. River dams, subsidence, and sea‐level rise have had a comparable influence on reduced delta growth over the past decades, but if we follow RCP8.5 to 2100, more than 85% of delta land loss will be caused by climate‐change driven sea‐level rise, resulting in a loss of ∼5% of global delta land. Plain Language Summary: River deltas can erode and lose land from sea‐level rise. Here we make model predictions of the effects of sea‐level rise for global delta land area change up to 2100. Our model is validated against observations of delta land area change from 1985–2015. For 2100, we find that most climate change scenarios lead to net delta land loss. Worst‐case scenarios for 2100 lead to a global river delta land loss of ∼5% of delta land, at a rate of 1, 000 km 2 per year. Key Points: Model of river delta response to sea level rise and river sediment applied to 6, 402 deltas and tested against land area change observations Projections suggest net delta land loss for GMSLR >5.5 mm/yr, and for RSLR under IPCC RCP4.5 and RCP8.5 by 2100 Climate‐change driven sea‐level rise will likely exceed the effects of dams and subsidence on global delta land loss by 2100